A Two-Level Factorial Design for Screening Factors that Influence the Growth of Bacillus sp. Strain UPM2021n isolated from a Mangrove Sediment on Acrylamide (Asian Journal of Plant Biology, 2022)
Acrylamide; a neurotoxicant, is an emerging pollutant of global importance. As a strategy for bioremediation, the breakdown of acrylamide by the action of microbes has seen a gradual but consistent increase in attention all over the world. An acrylamide-degrading bacterium tentatively identified as Bacillus sp. strain UPM2021n was screened for significant parameters contributing to optimized growth on acrylamide using a two-level factorial design. The two-level factorial design was adopted in screening of five independent factors influencing the growth of the bacterium on acrylamide. These factors include pH, temperature, incubation time, acrylamide concentration and glucose concentration.  A total of 32 experiments with three replications of the centre points were carried out. The two-level factorial design was successful in finding important contributing parameters in the  growth of this bacterium on acrylamide, which were pH and incubation time (p
Keywords: Acrylamide; Bacillus sp.; Bioremediation; Screening; Two-level factorial